Polybivalency and disordered proteins in ordering macromolecular assemblies. (January 2015) - Barbar, Elisar; Nyarko, Afua
Graphical abstract: Highlights: IDPs form polybivalent scaffolds that provide mutual enhancement of affinity for additional ligands, as well as for coiled-coil or self-association interactions. Bivalency compensates for unfavorable steric and enthalpic interactions. Bivalency is not accompanied by a detectable change in structure or NMR measured dynamics. The polybivalent nature of the scaffold produces an assemblage that is suitably stable even when the association constant of any single ligand, or coiled-coil, is moderate to weak. The polybivalent assemblage function in providing a high degree of regulatory flexibility and functional adaptability. Abstract: Intrinsically disordered proteins (IDPs) are prevalent in macromolecular assemblies and are thought to mediate protein recognition in complex regulatory processes and signaling pathways. The formation of a polybivalent scaffold is a key process by which IDPs drive early steps in macromolecular assemblies. Three intrinsically disordered proteins, IC, Swallow and Nup159, are core components, respectively, of cytoplasmic dynein, bicoid mRNA localization apparatus, and nuclear pore complexes. In all three systems, the hub protein LC8 recognizes on the IDP, short linear motifs that are fully disordered in the apo form, but adopt a β-strand when bound to LC8. The IDP/LC8 complex forms a bivalent scaffold primed to bind additional bivalent ligands. Scaffold formation also promotes self-association and/or higher order organization of the IDP components at a site distant from LC8 binding. Rigorous thermodynamic analyses imply that association of additional bivalent ligands is driven by entropic effects where the first binding event is weak but subsequent binding of additional ligands occurs with higher affinity. Here, we review specific examples of macromolecular assemblies in which polybivalency of aligned IDP duplexes not only enhances binding affinity and results in formation of a stable complex but also compensates unfavorable steric and enthalpic interactions. We propose that polybivalent scaffold assembly involving IDPs and LC8-like proteins is a general process in the cell biology of a class of multi-protein structures that are stable yet fine-tuned for diverse cellular requirements.